Marett og mana - Tybjerg, Tove (Religionsvidenskabeligt Tidsskrift, 2018)
English abstract: Robert Ranulph Marett’s (1866-1943) name is closely identified with the mana-concept. In some influential essays around 1900 and in critical dialogue with Tylor and Frazer, Marett proposed to use ‘mana’ as a technical term. Many were persuaded by Marett’s argument, but used the mana-concept in such a broad and heterogenous way, that it was soon deemed unfit for scientific use. As a result of Marett being more or less forgotten afterwards, few have been aware, that Marett’s arguments are more sophisticated than is usually acknowledged. Danish historians of religion have taken a more vivid interest in mana and the mana-concept; on a different basis, some of the issues – discussed in Denmark in connection with the mana-concept – are now under debate in ‘New animism’. Dansk resume: Robert Ranulph Maretts (1866-1943) navn er tæt knyttet til begrebet mana. I kritisk dialog med Tylor og Frazer argumenterede Marett i nogle skelsættende essays omkring år 1900 for indførelse af mana som teknisk term. Mange tog mana-begrebet til sig, men anvendte det så bredt og forskelligartet, at det hurtigt blev anset for ubrugeligt. At Marett siden blev mere eller mindre glemt, har medført, at man i almindelighed ikke har været tilstrækkelig opmærksom på nuancerne i Maretts argumentation. Det gælder dog ikke i dansk religionsvidenskab, hvor diskussionen af mana og mana-begrebet har været mere omfattende; problemstillinger, som i Danmark blev drøftet i forbindelse med mana-begrebet, er på et andet grundlag til diskussion i nutidens ‘New animism’.